SISTEM INFORMASI PELAPORAN KEGIATAN FUNDRAISING DI BAITULMAL FKAM MENGGUNAKAN PHP DAN DATABASE MYSQL UNTUK MENGGANTIKAN PELAPORAN BERBASIS EXCEL - Didik Nugroho, Ari Wahyono, Sri Siswanti, (Jurnal Ilmiah SINUS, 2015)
Baitulmal Â FKAM an agency that manages the charity, donation, Charity, Endowment and Hisbah. Reporting fundraising activities using Excel is not suitable to manage donor data in large quantities purpose of this study is to create an information system reporting fundraising activities in treasury FKAM to replace excel based reporting. Data were collected through observation, interviews and through the literature and report data documentation. information systems are built using PHP and MySql database. research is the realization of a system of information reporting fundraising activities in treasury FKAM using PHP and MySQL database.Keyword :Sistem Informasi, fundraising,Â  PHP, MySql